Structural and kinetic description of cytochrome c unfolding induced by the interaction with lipid vesicles. - Pinheiro, T; Elöve, G; Watts, A; Roder, H (1997)
The interaction of cytochrome c with anionic lipid vesicles of DOPS induces an extensive disruption of the native structure of the protein. The kinetics of this lipid-induced unfolding process were investigated in a series of fluorescence- and absorbance-detected stopped-flow measurements. The results show that the tightly packed native structure of cytochrome c is disrupted at a rate of approximately 1.5 s-1 (independent of protein and lipid concentration), leading to the formation of a lipid-inserted denatured state (DL). Comparison with the expected rate of unfolding in solution (approximately 2 x 10(-3) s-1 at pH 5.0 in the absence of denaturant) suggests that the lipid environment dramatically accelerates the structural unfolding process of cytochrome c. We propose that this acceleration is in part due to the low effective pH in the vicinity of the lipid headgroups. This hypothesis was tested by comparative kinetic measurements of acid unfolding of cytochrome c in solution. Our absorbance and fluorescence kinetic data, combined with a well-characterized mechanism for folding/unfolding of cytochrome c in solution, allow us to propose a kinetic mechanism for cytochrome c unfolding at the membrane surface. Binding of native cytochrome c in water (NW) to DOPS vesicles is driven by the electrostatic interaction between positively charged residues in the protein and the negatively charged lipid headgroups on the membrane surface. This binding step occurs within the dead time of the stopped-flow experiments (<2 ms), where a membrane-associated native state (NS) is formed. Unfolding of NS driven by the acidic environment at the membrane surface is proposed to occur via a native-like intermediate lacking Met 80 ligation (MS), as previously observed during unfolding in solution. The overall unfolding process (NS --> DL) is limited by the rate of disruption of the hydrophobic core in MS. Equilibrium spectroscopic measurements by near-IR and Soret absorbance, fluorescence, and circular dichroism showed that DL has native-like helical secondary structure, but shows no evidence for specific tertiary interactions. This lipid-denatured equilibrium state (DL) is clearly more extensively unfolded than the A-state in solution, but is distinct from the unfolded protein in water (UW), which has no stable secondary structure.